The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/jacs.5b10980
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Reactivity Relationships in Lithiated Evans Enolates: Influence of Aggregation and Solvation on the Stereochemistry and Mechanism of Aldol Additions

Abstract: Aldol additions to isobutyraldehyde and cyclohexanone with lithium enolates derived from acylated oxazolidinones (Evans enolates) are described. Previously characterized trisolvated dimeric enolates undergo rapid addition to isobutyraldehyde to give a 12:1 syn:syn selectivity in high yield along with small amounts of one anti isomer. The efficacy of the addition depends critically on aging effects and the reaction quench. Unsolvated tetrameric enolates that form on warming the solutions are unreactive toward i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 103 publications
1
26
0
2
Order By: Relevance
“…8 Rate and computational studies implicated monomer-based transition structure 6 . We would be remiss if we did not also mention that computational studies suggested that the H–H interaction highlighted in 6 causes facial selectivity rather than an explicit interaction of the aldehyde with the benzyl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…8 Rate and computational studies implicated monomer-based transition structure 6 . We would be remiss if we did not also mention that computational studies suggested that the H–H interaction highlighted in 6 causes facial selectivity rather than an explicit interaction of the aldehyde with the benzyl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[61] Über die faszinierende Chemie der Aggregate ist noch viel zu lernen. Vielleicht ist diese Rückbesinnung auf die Grundlagen sinnvoll, mit einem Fokus auf einem Alkalimetallenolat in einer chiralen Umgebung.D ie Stereoselektivitätd er Enolisierung sollte lçsbar sein, das vielleicht grçßte Problem ist aber die Kontrolle der Aggregatzustände.…”
Section: Zusammenfassung Und Ausblickunclassified
“…Vielleicht ist diese Rückbesinnung auf die Grundlagen sinnvoll, mit einem Fokus auf einem Alkalimetallenolat in einer chiralen Umgebung.D ie Stereoselektivitätd er Enolisierung sollte lçsbar sein, das vielleicht grçßte Problem ist aber die Kontrolle der Aggregatzustände. [61] Über die faszinierende Chemie der Aggregate ist noch viel zu lernen. Das im Zusammenhang mit Lithium und anderen Alkalioder Erdalkalimetallen entstehende Bild lässt interessanterweise darauf schließen, dass sich das chemische Verhalten am besten im Bereich der Koordinationschemie betrachten lässt, und nicht als vereinfachendes Problem von Aciditätu nd Basizität.…”
Section: Zusammenfassung Und Ausblickunclassified
“…9,10 By contrast, few experimental probes of mechanism have been carried out with either simple boron enolates 11 or oxazolidinone-based variants. 6,1215 On the heels of investigations of lithium-based aldol additions of Evans enolates, 12 we undertook structural and mechanistic studies of the boron variant in Scheme 1. 16 …”
Section: Introductionmentioning
confidence: 99%